BARGAIN OF MANATÍES (TRICHECHUS MANATUS) IN LIFE FREE ACCORDING TO EXPERIMENTS OF PREFERENCE AS A BASE FOR THE CAPTURE THROUGH THE TECHNIQUE OF ENCIERRO-TRAMPA, NATIONAL PARK TORTUGUERO, LIMÓN COSTA RICA - Gómez-Lépiz, Alexander (2010)
This study determined the preference of the manatees for some food resources, which constitute their diet in the region. The preference of the herbivore is typically shown through the "cafeteria feeding trials" technique: the animals are left to choose freely among the plants available for them. In order to evaluate the preference of the manatees through this technique, plants normally consumed by the manatee were offered (Paspalum repens, Urochloa mutica, Hydrocotyle ranunculoides y Eichhornia crassipes) in the study area, next to other vegetables normally consumed by humans, which are usually offered at a Zoo as part of their diet. Of all the plants offered, the grass P. repens was the preferred plant, which was successfully used to evaluate the preliminary structure lock up-trap where the manatees entered. The preference for this plant could be attributed to characteristics that were not evaluated for this study, such as palatability, microelements, and/or texture.